Victimization analysis model of user network behavior based on network traffic - Shengli ZHOU; Xiaoyang XU (Dianxin kexue)
The analysis of network victimization is of great significance to the prevention and control of telecom fraud.By studying the network traffic generated by the interaction between users and websites, a victimization identification model of telecom fraud crime based on network behavior flow analysis was proposed, the association rules between different behavior characteristics were analyzed, the behavior sequence features were reconstructed, and the victimization of network behavior sequence with random forest algorithm was evaluated.Based on the network behavior data set of public security organs, the experiment proves that the model can effectively improve the recognition accuracy of network behavior victimization.